2013
DOI: 10.1371/journal.pone.0081009
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Humor Experiences from Brain Activity of People Viewing Comedy Movies

Abstract: Humans naturally have a sense of humor. Experiencing humor not only encourages social interactions, but also produces positive physiological effects on the human body, such as lowering blood pressure. Recent neuro-imaging studies have shown evidence for distinct mental state changes at work in people experiencing humor. However, the temporal characteristics of these changes remain elusive. In this paper, we objectively measured humor-related mental states from single-trial functional magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…The anterior STG was connected with social-conceptual knowledge, the MPFC and anterior ITG with context-appreciation, the amygdala and hippocampus with strength of irony perceptions, and the DLPFC with the degree of humorousness experienced ( Akimoto et al, 2014 ). Other work presented observations that the right DLPFC and temporal-lobe areas seem to govern anticipation of humorous events ( Sawahata et al, 2013 ). In a final noteworthy study, the frontal pole was activated during humor in comedy clips, possibly because the humor extended over a longer time in those clips ( Iidaka, 2017 ; Jaaskelainen et al, 2016b ).…”
Section: Naturalistic Stimuli In Neuroimaging Studies Of Social Cognimentioning
confidence: 99%
“…The anterior STG was connected with social-conceptual knowledge, the MPFC and anterior ITG with context-appreciation, the amygdala and hippocampus with strength of irony perceptions, and the DLPFC with the degree of humorousness experienced ( Akimoto et al, 2014 ). Other work presented observations that the right DLPFC and temporal-lobe areas seem to govern anticipation of humorous events ( Sawahata et al, 2013 ). In a final noteworthy study, the frontal pole was activated during humor in comedy clips, possibly because the humor extended over a longer time in those clips ( Iidaka, 2017 ; Jaaskelainen et al, 2016b ).…”
Section: Naturalistic Stimuli In Neuroimaging Studies Of Social Cognimentioning
confidence: 99%
“…How does contextual information, such as social interactions or empathetic identification processes, influence the processing of perceived emotions? Additional relevant stimulus annotations are already available 3 and further descriptions of this stimulus can enhance its utility as a reference for building upon previous movie stimulus studies on, for example: social perception 24 , facial expression 25 , fear 26 , humor 27 , sadness/amusement 28 , disgust/amusement/sexual arousal 29 , sadness 30 , happiness/sadness/disgust 31 , and emotional valence 32 .…”
Section: Technical Validationmentioning
confidence: 99%
“…Recent neuroimaging studies have revealed physiological evidence for a relationship between mental states and experiencing humor while watching a film. 22 Their results on predicting upcoming humor, or anticipating humorous events, suggest that to induce laughter efficiently it is important that the viewer expect a humorous event and then to give him or her a punch line within a few seconds. The authors recommended further investigation to determine whether or not the findings are valid for various types of humor.…”
Section: Discussionmentioning
confidence: 99%